Comparison of Two Real-Time PCR Assays Targeting Ribosomal Sequences for the Identification of Cystoisospora belli in Human Stool Samples - Martin Blohm; Andreas Hahn; Ralf Matthias Hagen; Kirsten Alexandra Eberhardt; Holger Rohde; Gérard Leboulle; Torsten Feldt; Fred Stephen Sarfo; Veronica Di Cristanziano; Hagen Frickmann; Ulrike Loderstädt (Pathogens, 2021)
Cystoisospora (C.) belli is a coccidian parasite associated with acute or chronic gastroenteritis in immunocompromised patients. Dissatisfactory sensitivity of microscopy as the diagnostic standard approach has been described. Here, we comparatively evaluated two real-time PCRs targeting ribosomal RNA gene sequences of C. belli in stool in a test comparison without a reference standard applying latent class analysis. Therefore, 1000 stool samples from Ghanaian HIV (human immunodeficiency virus) patients (n = 905) as well as military returnees from the tropics (n = 95) were assessed by both assays in parallel. After the exclusion of 33 samples showing PCR inhibition, 29 and 33 positive results were recorded with the 5.8S rRNA gene/ITS-2 sequence PCR and the ITS-2 sequence PCR, respectively, resulting in an accuracy-adjusted prevalence of 3.2%. Nearly perfect agreement between both assays was indicated by Fleiss’ kappa of 0.933 with sensitivity and specificity of 92.8% and 100% as well as 100% and 99.8% for the 5.8S rRNA gene/ITS-2 sequence PCR and the ITS-2 sequence PCR, respectively. Both assays proved to be suitable for the diagnosis of C. belli in human stool samples with slightly better sensitivity of the ITS-2 sequence assay, while the 5.8S rRNA gene/ITS-2 sequence PCR may be considered for confirmatory testing.